Understanding Alignments and Mis-Alignments of Values to Better Craft Institutions in the Pastoral Drylands - Addison, Jane; Brown, Colin; Pavey, Chris R.; Lkhagvadorj, Enkh-Orchlon; Bukhbat, Duinkherjav; Dorjburegdaa, Lkhagvadorj (Frontiers in Sustainable Food Systems, 2020)
Tensions in values between dryland pastoralists and non-pastoralists, and often between pastoralists themselves, are common globally. The re-imagining of grazed landscapes must recognize that current pastoralists have their own visions of what pastoralism does, can and should provide to both themselves and society at large. ‘Disrupters’ may rapidly and permanently alter the social-ecological system but understanding pastoralist visions and values may help highlight effective and ethical mechanisms by which we can gently shift current systems towards socially re-imagined systems. Here we draw on two case studies from grazed dryland landscapes to highlight the ways in which understanding pastoralist values and visions could help with this shift. We choose case studies from contrasting institutional, cultural and economic contexts to better explore fit-for-purpose policy options. The first case study is from the typical and desert steppe of Mongolia, and the second from dryland Australia. Drawing on primary data and the literature, we explore in these contexts: what constitutes a meaningful livelihood for pastoralists? how might these imaginings align (or misalign) with the imaginings of the broader population? what inertia against future societal imaginings might a potential misalignment create? and how might policy provide a push (or pull) against such an inertia? We show that context-specific understandings of pastoralist values and visions can highlight appropriate policy options to encourage the movement of social-ecological systems towards those that are more socially desirable. However, the design of these options requires understanding unique combinations of pastoral and societal values, biophysical parameters and institutional contexts.